2019
DOI: 10.1101/797431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase separation by ssDNA binding protein controlledviaprotein-protein and protein-DNA interactions

Abstract: Bacterial single stranded (ss) DNA-binding proteins (SSB) are essential for the replication and maintenance of the genome. SSBs share a conserved ssDNA-binding domain, a less conserved intrinsically disordered linker (IDL) and a highly conserved C-terminal peptide (CTP) motif that mediates a wide array of protein-protein interactions with DNA-metabolizing proteins. Here we show that the E. coli SSB protein forms liquid-liquid phase separated condensates in cellular-like conditions through multifaceted interact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…For a more in-depth review of BR-body function and phylogenetic distribution, see Muthunayake et al (4). (21) In vitro (18) In vitro (18) In vitro (18) In vitro (22) In vitro (22) In vitro (22) In vitro (47) In vitro (23) In vivo In vitro spherical (23,24,26) In situ icosahedral (95)(96)(97)(98) In situ (25,29) In vitro (23) In vivo (91) In vitro (26) In vitro (23,24,26) ND…”
Section: Current Evidence Demonstrates That Llps May Mediate Subcellumentioning
confidence: 99%
See 1 more Smart Citation
“…For a more in-depth review of BR-body function and phylogenetic distribution, see Muthunayake et al (4). (21) In vitro (18) In vitro (18) In vitro (18) In vitro (22) In vitro (22) In vitro (22) In vitro (47) In vitro (23) In vivo In vitro spherical (23,24,26) In situ icosahedral (95)(96)(97)(98) In situ (25,29) In vitro (23) In vivo (91) In vitro (26) In vitro (23,24,26) ND…”
Section: Current Evidence Demonstrates That Llps May Mediate Subcellumentioning
confidence: 99%
“…Single-stranded DNA binding protein (SSB) stabilizes single-stranded DNA (ssDNA) and recruits proteins essential for DNA replication, repair, and recombination (49). This NAP is a good candidate for condensate formation through LLPS because it forms phase-separated droplets, is promiscuous in its binding interactions, and contains an IDR (22). A combination of turbidity measurements and fluorescence imaging found that SSB forms liquid-like droplets in vitro.…”
Section: Dna Repairmentioning
confidence: 99%
“…Given Pol IV is constitutively elevated in our imaging strain, the increase in static Pol IV molecules near lesion-stalled replisomes is primarily due to decreased outflux of Pol IV from the replication fork. During replication a steady state level of SSB is present on the lagging strand, forming a condensate of SSB-Ct (Harami et al, 2019), yet individual SSB molecules are rapidly turned over because the complete synthesis of an Okazaki fragment takes only ~2 seconds, limiting the average lifetime of lagging-strand SSB molecules to around 1 second (Ogawa and Okazaki, 2002;Wu et al, 1992). This timescale may be too short to allow for association of Pol IV with SSB.…”
Section: Switching Between Replication-and Repair-competent Ssb Condementioning
confidence: 99%
“…However, these behaviors are almost impossible to observe in tiny bacteria using conventional microscopy. Thus, bacterial condensate formation has been demonstrated by in vitro reconstitution, by visualizing the building blocks with fluorescence or differential interference contrast microscopy, and by correlating these LLPS activities in vitro with the behaviors of foci in cells (17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the in vitro concentrations and environmental conditions (salt concentrations, pH, temperature, crowding agents) under which components phase separate have been measured (17,19,(21)(22)(23)(24)(25)27). The liquid-like behavior of condensates has been tested by fluorescence recovery after photobleaching (FRAP) and by observing droplet fusion events (17,21,24,26,28).…”
Section: Introductionmentioning
confidence: 99%